Hubungan tingkat pengetahuan keluarga tentang Hemodialisa dengan tingkat kecemasan keluarga Yang anggota keluarganya menjalani terapi Hemodialisa - Arosa, Fyl Asro; -, Jumaini -; Woferst, Rismadefis - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determined the level of familyâs knowledge with the level of anxiety whose famylyâs members undergoing hemodialysis therapy. The research method was a cross sectional with analytic approach. The study was conducted at hemodialysis room of Arifin Achmad Hospital in Pekanbaru involving 52 respondents. The sampling method used convinence sampling (accidental sampling). Measuring instrument used was a questionnaire that had been tested for validity and reliability. The analysis used univariate and bivariate with chi square test. Based on the results, the level of family knowledge about hemodialysis is good enough as many as 28 respondents (53.8%), less in 15 respondents (28.8%) and good in 9 respondents (17.4%). This research can be concluded that no significant relationship between the level of familyâs knowledge about hemodialysis with the level of anxiety that members of undergoing hemodialysis therapy (p value 0,002). The results of this research recommends nurses to provide health education aboutÂ  hemodialysis to familyâs member undergoing hemodialysis therapy wich Chronic Renal Failure (CRF). Keywords: hemodialysis, anxiety, familyâs, knowledge. Â